Daily strategies to improve music literacy in the band classroom - Poort, Jeffrey David (Kansas State University, 2022)
In my videos you will see three different activities featuring a high school band ensemble. Through these activities I have attempted to better equip my students with music literacy strategies to address what I have perceived as a deficiency in my pedagogy and to set up the students to have more efficacy and independence in their own musical learning. In the first lesson and video, I aim to equip the students with a structured sight-reading system to enable them to decode musical passages and composer intent in hopes of a stronger initial performance. Highlighted in the second video, I have the students put this sight-reading system to practice in small ensembles, while under a time limit and before a classroom performance and review. Lastly, in the third lesson and video, I introduce the first iteration of a daily “literacy ritual,” inspired by Robert Sheldon. I endeavor to strengthen the music literacy of the entire ensemble through new approaches via the above activities. My time working on my Master’s degree at Kansas State University has inspired me to critically consider my instructional methods and the needs of the students entrusted to me. Am I teaching the way I do because it worked for me as a student, that is how I have seen others do it, or am I truly considering the needs of the students in front of me and adjusting my practice to meet them where they are? As a result of deep self-reflection throughout my studies, I uncovered a habit of not reviewing key concepts, instead teaching by rote to the detriment of a number of students. Similarly, I was inspired to consider my daily activities, such as warmups. Are the warmups I assign connecting to the content I deliver or are they just another stale and time-consuming routine while I complete the attendance roll for the main office? By thoughtfully crafting and customizing daily warmup activities, I discovered how I can still check the box of basic skill development while also setting students up for greater success with the ensemble literature to follow. In these ways and more, I have become better equipped as an educator to serve my students.
Keywords: Music literacy; Band; Music reading; Sight reading; Music decoding